(untitled) (Bangladesh Journal of Urology, 2020)
Objectives: To compare the outcomes of early primary endoscopic realignment and suprapubic cystostomy with the outcomes of delayed reconstruction in the management of posterior urethral injury. Methods: This is a quasi-experimental prospective study Conducted in the Urology department Dhaka medical college and hospital from January 2009 to December 2010. Atotal of 60 consecutive patients were selected for this study and inclusion criteria, male patients and age 18years and above. Posterior urethral injury resulting in distraction defect and urethral injury with pelvic fracture. Group-A, 28 patients underwent early primary endoscopic realignment after initial suprapubic urinary diversion and Group-B, 32 patients underwent primary suprapubic urinary diversion and delayed urethral reconstruction after 3 months of injury. Results: After procedure 21(75%) out of 28 patients in Group-A developed stricture 12(42.9%) had simple and short segment stricture and 7(32.1%) had simple and long segment stricture, while in Group-B 12(37.5%) patients developed simple and short segment stricture. All of the patients in Group-A had minimum blood loss during operation. While, majority (81.3%) of patients in Group-B had a history of maximum blood loss. None of the patients in Group-A developed incontinence throughout the observations period (from removal of catheter to 9 months), while 15.6% of the patients in Group-B had incontinence at removal of catheter after anastomotic urethroplasty and at 3 month. The incontinence further increased to 18.8% at 6 and 9 months. Complaints of impotence were significantly less in Group-A than that in Group-B throughout the period of observation (14.3% vs. 37.5%, p = 0.042; 14.3% vs. 37.5%, p = 0.042 and 14.3% vs. 37.5%, p = 0.042). At removal of urethral catheter, stricture formation was observed and statistically there was no difference in Group-A and Group-B (14.3% vs. 21.9% in Group-B, p = 0.448). At month 3, stricture formation was significantly higher in Group-A than that in Group-B (42.9% vs. 15.6%, p = 0.020). At month 6, about 18% of patients in Group-A had stricture, but none of patients in Group-B was found so (p = 0.018). Conclusions: Early primary endoscopic realignment of traumatic posterior urethral disruption is a simple, less traumatic, safe, and rapid technique. It provides a low morbidity and less postoperative complications. Though recurrent stricture formation is higher but the strictures are simple and short and amenable to be corrected endoscopically. It may be considered as initial therapy in the management of posterior urethral distraction defect over suprapubic cystostomy with delayed reconstruction. Bangladesh Journal of Urology, Vol. 17, No. 1, Jan 2014 p.29-35